(untitled) - Tom Hutchinson (Oxford, 1993)
The book covers a lookback syllabus, a grammar-based analytical approach, skills work, project work, cross-cultural and cross-curricular studies, learner training
Keywords: english language - spoken english - problems, exercises, etc,english language - textbooks for foreign speakers,listening - problems, exercises, etc